Environmental Innovation, War of Attrition and Investment Grants - Michele Moretto; Cesare Dosi (Fondazione Eni Enrico Mattei (FEEM), 2004)
The paper analyses the timing of spontaneous environmental innovation when second-mover advantages, arising from the expectation of declining investment costs, increase the option value of waiting created by investment irreversibility and uncertainty about private payoffs. We then focus on the design of public subsidies aimed at bridging the gap between the spontaneous time of technological change and the socially desirable one. Under network externalities and incomplete information about firms switching costs, auctioning investment grants appears to be a cost-effective way of accelerating pollution abatement, in that it allows targeting grants instead of subsidizing the entire industry indiscriminately.
Keywords: Q28; O38; 330; Environmental innovation; Investment irreversibility; Network externalities; Investment grants; Second-price auction; Umwelttechnik; Investitionspolitik; Investition; Netzeffekt; Auktionstheorie